2015
DOI: 10.1155/2015/260126
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Knowledge of Sexually Transmitted Infections among Secondary School Adolescents in Ado Ekiti, South Western Nigeria

Abstract: Objective. To determine the awareness and knowledge of sexually transmitted infections among adolescents in Ado, South Western Nigeria. Methods. The study was a descriptive cross-sectional design. Five hundred and fifty adolescents selected from public and private secondary schools in Ado Local Government Area of Ekiti State were recruited using a multistage sampling technique. Results. Four hundred and ninety-nine (92.4%) respondents had heard about sexually transmitted infections before, the three most impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
61
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 12 publications
19
61
3
2
Order By: Relevance
“…The current study finding was in agreement with that of Amu & Adegun [23] in Nigeria, who conducted a study to assess awareness and knowledge of sexually transmitted infections among secondary school adolescents and found that nearly all of the respondents had good knowledge related to STDs. This finding is consistent with that of a study carried out in Malaysia, by Awang et al [24] who mentioned that 92% of the adolescents reported awareness of STDs.…”
Section: Discussionsupporting
confidence: 91%
“…The current study finding was in agreement with that of Amu & Adegun [23] in Nigeria, who conducted a study to assess awareness and knowledge of sexually transmitted infections among secondary school adolescents and found that nearly all of the respondents had good knowledge related to STDs. This finding is consistent with that of a study carried out in Malaysia, by Awang et al [24] who mentioned that 92% of the adolescents reported awareness of STDs.…”
Section: Discussionsupporting
confidence: 91%
“…A similar finding has been published by Amu and Adegun in their study among secondary school adolescents. [10]…”
Section: Discussionmentioning
confidence: 99%
“…Our review of literature shows a similar finding in many studies conducted at different geographic locations. [5910111213]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As those people who do not know the symptoms may fail to recognize their need and so may not seek help (Amu and Adegun, 2015).…”
Section: Introductionmentioning
confidence: 99%